2015
DOI: 10.1111/cge.12613
|View full text |Cite
|
Sign up to set email alerts
|

X‐chromosome inactivation in female patients with Fabry disease

Abstract: Fabry disease (FD) is an X-linked genetic disorder caused by the deficient activity of lysosomal α-galactosidase (α-Gal). While males are usually severely affected, clinical presentation in female patients may be more variable ranging from asymptomatic to, occasionally, as severely affected as male patients. The aim of this study was to evaluate the existence of skewed X-chromosome inactivation (XCI) in females with FD, its concordance between tissues, and its contribution to the phenotype. Fifty-six females w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
248
3
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(291 citation statements)
references
References 60 publications
6
248
3
16
Order By: Relevance
“…Moreover, until a few years ago the inactivation of the X chromosome was thought to be random, but today this concept has been revised. It was observed that in some females, the X chromosome inactivation is not random in all tissues but some of them show a skewed inactivation to the wild type X chromosome or the mutated one -phenomenon that, still today, is without an explanation (Echevarria et al, 2015). This results in a great clinical heterogeneity ranging from the absence of the manifestations to a severity comparable to the one of the males affected by Fabry disease (Whybra et al, 2001;MacDermot et al, 2001;Wilcox et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, until a few years ago the inactivation of the X chromosome was thought to be random, but today this concept has been revised. It was observed that in some females, the X chromosome inactivation is not random in all tissues but some of them show a skewed inactivation to the wild type X chromosome or the mutated one -phenomenon that, still today, is without an explanation (Echevarria et al, 2015). This results in a great clinical heterogeneity ranging from the absence of the manifestations to a severity comparable to the one of the males affected by Fabry disease (Whybra et al, 2001;MacDermot et al, 2001;Wilcox et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, female participants in this study were not tested for X chromosome inactivation and prior studies have shown that female patients who seek medical attention are more severely affected by FD than their counterparts. 29 Otherwise, with exception of history of stroke being an independent predictor of WMHV in the 5th decade of life, the profile of WMH burden determinants appears to reflect the spectrum of accumulating comorbidities typical in the lifetime of FD. Overall, caution should be exercised in interpreting the results of subset analyses, which were exploratory in nature and based on a relatively small number of patients included in per stratum analysis, limiting the power to discover significant associations with the outcome.…”
mentioning
confidence: 89%
“…In FD heterozygotes, the α-GalA activities are often borderline normal or normal due to random X-chromosomal inactivation [3]. Our findings suggest that this biomarker may improve initial diagnose of clinically relevant FD, particularly in female patients.…”
Section: Discussionmentioning
confidence: 72%
“…These studies are limited since the sample size is relatively small and larger studies are needed to confirm our findings. In addition, the degree of random X-chromosomal inactivation is the most prominent epigenetic factor that determines if a Type 1 Classic or Type 2 Later-Onset heterozygote will be symptomatic [3]. It would be useful to correlate the degree of "Lyonization" with the LysoGb3 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation